2020
DOI: 10.3390/nu12061842
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects of Coffee: Mechanism Unraveled?

Abstract: The association of habitual coffee consumption with a lower risk of diseases, like type 2 diabetes mellitus, chronic liver disease, certain cancer types, or with reduced all-cause mortality, has been confirmed in prospective cohort studies in many regions of the world. The molecular mechanism is still unresolved. The radical-scavenging and anti-inflammatory activity of coffee constituents is too weak to account for such effects. We argue here that coffee as a plant food has similar beneficial properties to man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 102 publications
(138 reference statements)
3
43
0
1
Order By: Relevance
“…Across previous CaffEQ studies, caffeine was consumed mainly in coffee, a habit also observed in Brazil [ 6 , 7 , 8 ]. Globally, habitual coffee consumption ranges from about 1 to more than 5 cups per day, which indicates that the daily dose is defined by several reasons, like lifestyle, gender, expectance of caffeine effects, culture, genetics, health effects, among others [ 2 , 36 , 57 ]. Most of our sample (69%) are used to consuming 2 or 3 portions of coffee daily ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Across previous CaffEQ studies, caffeine was consumed mainly in coffee, a habit also observed in Brazil [ 6 , 7 , 8 ]. Globally, habitual coffee consumption ranges from about 1 to more than 5 cups per day, which indicates that the daily dose is defined by several reasons, like lifestyle, gender, expectance of caffeine effects, culture, genetics, health effects, among others [ 2 , 36 , 57 ]. Most of our sample (69%) are used to consuming 2 or 3 portions of coffee daily ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Caffeine, one of the most consumed and widely accepted neurostimulants, is also a powerful agent used in life science research. Due to its pleiotropic effects [ 163 ], caffeine is an active modulator of different enzymes and their regulatory pathways, which include important molecular players such as TOR kinases or DNA damage checkpoint kinases. Many of the studies reviewed here, which made use of the interaction between caffeine and S. cerevisiae, contributed to elucidating molecular mechanisms involved in biologic processes of general concern, such as DNA repair mechanisms, cancer, or aging.…”
Section: Discussionmentioning
confidence: 99%
“…No dose-dependent conclusion can be drawn from the changes observed in the 0.29 g/kg BW group, as the highest dose did not exacerbate the parameters measured. Contrarily, the consumption of coffee has been reported to decrease liver enzymes associated with liver damage and has shown protective effects attributed to its polyphenol content [ 38 , 39 , 40 , 41 , 42 , 43 ]. There were favorable significant reductions in liver enzymes (ALP and ALT) and lipid profile indicator (triglyceride) in the low male dose group but no trend was evident in the higher dose groups except in the female triglyceride level when given the high dose.…”
Section: Discussionmentioning
confidence: 99%
“…The interactions between the different components present in both coffee and TA and additionally with food may have exerted their effects on the parameters measured in this study. Both coffee and TA are made up of various phytochemicals, such as caffeine and polyphenols, found in coffee, and eurycomanone, a major compound found in TA [ 1 , 39 , 40 ]. Caffeine has been well studied and is reported to have a high tolerance dose of 400 mg/day in human [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%